Plato and the cave allegory. An interpretation beginning with verbs of knowledge - Calabrese, Claudio César (My University, 2020)
In this paper we study the organization of the allegory of the cavern through the investigation of knowledge verbs. First, we briefly follow the interpretations of the allegory of the cave that we consider most significant and our perspective: all are valid provided that each does not deny the others. At our core we analyze the verbs of knowledge: how they relate to each other and what structure of knowledge they establish. In the conclusion, we affirm that the verbs do not present a vision of being as "what is", but as "what is being"; this means, with respect to the allegory, that the relation between being and intelligibility means a pathway of mutual equalization, which the prisoner of the cave goes through; nevertheless, the attempt to reach a comprehensive intelligence of the being requires one more step: to integrate the phenomena to the comprehension of the real thing.